1995
DOI: 10.1007/bf00401761
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of short- and long-term fatty acid infusion on insulin secretion in healthy subjects

Abstract: Our study investigates short- and long-term effects of infusion of non-esterified fatty acids (NEFA) on insulin secretion in healthy subjects. Twelve healthy individuals underwent a 24-h Intralipid (10% triglyceride emulsion) infusion at a rate of 0.4 ml/min with a simultaneous infusion of heparin (a bolus of 200 U followed by 0.2 U/min per kg body weight). After an overnight fast (baseline), at 6 and at 24 h of Intralipid infusion and 24 h after Intralipid discontinuation (recovery test), all subjects underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
123
1
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 19 publications
(10 reference statements)
3
123
1
4
Order By: Relevance
“…The prior increase of plasma NEFA concentrations resulted in higher plasma insulin concentrations during basal glucose and during glucose stimulation, with the first and second phase being exaggerated. Other studies also showed enhanced insulin secretion when plasma NEFA concentrations were increased for 20 min, 90 min or 5 h, by Intralipid and heparin in healthy volunteers [12,13,15]. A short-term (9-h) plasma NEFA increase induced insulin secretion in humans and this was sufficient to prevent an increase in plasma glucose concentrations [28].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The prior increase of plasma NEFA concentrations resulted in higher plasma insulin concentrations during basal glucose and during glucose stimulation, with the first and second phase being exaggerated. Other studies also showed enhanced insulin secretion when plasma NEFA concentrations were increased for 20 min, 90 min or 5 h, by Intralipid and heparin in healthy volunteers [12,13,15]. A short-term (9-h) plasma NEFA increase induced insulin secretion in humans and this was sufficient to prevent an increase in plasma glucose concentrations [28].…”
Section: Discussionmentioning
confidence: 90%
“…A short-term (9-h) plasma NEFA increase induced insulin secretion in humans and this was sufficient to prevent an increase in plasma glucose concentrations [28]. However, no hyperinsulinaemic response has been reported when plasma NEFA concentrations were increased for 5 h to 10 h [29,30] and this turned into an inhibitory effect after a very long-term increase (>24 h) [13,15]. In these studies, a wide range of plasma NEFA concentrations were reported, which may partly explain the divergence in insulin response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, circulating fatty acids, both observationally and experimentally, seem closely involved in the pathogenesis of type 2 diabetes [31,33]. Depending on chain length, fatty acids also stimulate insulin secretion [34,35], which may further aggravate hepatic insulin resistance [36]. The fall in NEFA after glucose challenge between the sites (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Administration of intralipid and heparin to raise plasma FFA results in an increased GSIS. 6,7 Experiments performed on perfused pancreas indicate that the insulinotropic action of FFA increases with their chain length and degree of saturation. 8 In contrast, long-term exposure to FFA increases basal and blunts GSIS.…”
Section: Short-term Effects Of Fatty Acids On Insulin Secretionmentioning
confidence: 99%